An Efficient Region of Interest-Based Hybrid Compression Technique for Medical Images - Seddeq. E. Ghrare , Khaled E. Gharari (Journal of Pure & Applied Sciences, 2018)
Medical images modalities are extensively adapted to diagnosis disease. These imaging modalities include computed tomography (CT), magnetic resonance imaging (MRI), ultrasound (US), and X-ray… etc. The problem associated with medical images is the storage space and bandwidth required for archiving and transmission of this kind of images. Thus image compression is a key factor to reduce the bit rate for transmission or storage while maintaining an acceptable reproduction quality. In this paper, an efficient ROI compression approach using hybrid lossy-lossless compression will be presented. This method is based on applying discreet wavelet transform (DWT) as a lossy method and grayscale and binary matrix (GSBM) coding algorithm as lossless method. The results show that the proposed method performs much better than Jpeg-lossless especially with smaller regions of interest.